PEMIKIRAN TENTANG HUKUM DAN MORAL DALAM FILSAFAT CINA PERIODE HAN AWAL (206 SM-6 M) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT . The relationship between law and moral is the one of the important problems of the philosophy of law. The complexity of the problems needs a comprehensive view that correlated with the concepts of man, society, politics, and ethics. The study of Chinese Philosophy in the Early Han time, with the Chinese philosophy character which tended to correlate with the philosophy of man and political ethics, is expected to give a contribution to the systematic studies of legal philosophy and comparative philosophy. This philosophical research is a library research, which is done in three steps: I: collecting and classifying data